(untitled) (Revista Electrónica REDINE, 2018)
From the perspective of marketing, the University Education Institutions need to define and know the educational market, to proceed to segment it and present an attractive academic offer. In this way, this essay presents its main attributes that demonstrate that it is a very competitive market, but at the same time regulated, because there are multiple offerers and demanders for educational services and the State creates the guidelines that assure it the largest portion of the market. In addition, the main characteristics offer and demand are presented and it is argued that segmentation is based on the duration of careers, territoriality and specialization.